Achieving Time-Sensitive Organizational Performance Through Mindful Use of Technologies and Routines - Gardner, John W.; Boyer, Kenneth K.; Ward, Peter T. (Organization Science, 2017)
Organizational performance is often dependent on the timing of critical processes and the simultaneous use of both technology and routines. Existing publications emphasize the importance of time sensitivity but also reflect divergent, untested perspectives. Prior works do not clearly explain or examine how different mechanisms are associated with achieving time-sensitive versus general (or non-time-sensitive) performance. We build on concepts from organizational mindfulness and organizational routines to address these gaps. Specifically, this paper examines how the mindful use of information technologies and adherence to specified routines are associated with both time-sensitive and general organizational performance. We employ split-group structural equation modeling based on high and low levels of information technology adoption to account for potential technology contingencies in performance. We use time-sequenced data from 262 U.S. hospitals to analyze two categories of clinical care quality: time-sensitive care and general care. The results indicate that mindful use of technologies is associated with both time-sensitive and general performance in contexts with high technology adoption but not in those with low adoption. In contrast, adherence to specified routines is associated with time-sensitive performance in contexts with low technology adoption but not in those with high adoption. The results also clarify that high levels of technology adoption and mindful use may at times assume the place of specified routines in their association with time-sensitive performance. Finally, we find evidence that continuous improvement may bridge adherence to specified routines and mindful use of technologies.